Pengaruh Penggunaan Media Kartu Kata Bergambar terhadap Kemampuan Membaca Permulaan Siswa Kelas I SDN 16 Mataram - Irda Hayyibi Ilmi; Darmiany; Setiani Novitasari (Mataram University, 2026)
This study was motivated by the low early reading ability of first-grade students at SDN 16 Mataram, where 56.25% of students were still limited to letter recognition and syllable reading due to the use of monotonous learning media. The purpose of the study was to measure the effect of picture word card media on early reading ability. A quantitative approach was used with a One-Group Pretest-Posttest design, involving all 17 first-grade students as a saturated sample. The instrument consisted of a performance test covering four indicators: letter recognition, syllables into words, words into simple sentences, and fluency and clarity of voice. Data were analyzed using Paired Sample T-Test via SPSS 27.0. The results showed an increase in the mean score from 40.93 (pretest) to 67.74 (posttest), with a Sig. (2-tailed) value of 0.000 < 0.05, thus H₀ was rejected and H₁ was accepted. It is concluded that there is a significant effect of using picture word card media on the early reading ability of first-grade students at SDN 16 Mataram.